Common errors in the use of English vocabulary with special reference to Malay ESL learners at Kolej Yayasan Terengganu / Salihah Abdullah - Abdullah, Salihah (2006)
This study examines some of the common vocabulary errors made by ESL learners. The data was obtained from three categories of the vocabulary errors, which include errors due to confusable pair word, errors due to semantic confusion and errors due to direct translation. Apart from analyzing the vocabulary errors, questionnaires were used to investigate students’ perception towards learning English. In the 3 categories, mother tongue interference accounted for the highest percentage of errors, followed by semantic confusion and confusable pair word. The findings from the questionnaire showed that the low proficiency of English was due to lack of exposure in using the language and insufficient grammar knowledge and practice. The possible cause of vocabulary errors were the result of interference from the LI and intralingual interference.